Nutritional requirements of Brachiaria and adaptation to acid soils - Rao, Idupulapati M.; Kerridge, Peter C.; Macedo, Manuel Cláudio Motta (International Center for Tropical Agriculture, 1996)
Most commercial Brachiaria species are adapted to low-fertility acid soils of the tropics. We describe, with examples, some of the attributes that enable them to adapt. These include the ability to (1) maintain root growth at the expense of shoot growth; (2) acquire and use both nitrate and ammonium forms of N; (3) acquire N through associative fixation; (4) acquire p through extensive root systems and association with vesicular-arbuscular mycorrhizae; and (5) acquire Ca through extensively branched roots with large numbers of root tips. Although Brachiaria species have much lower internal requirements, especially of p and Ca, than do other grasses such as Panicum maximum, they show interspecific differences, which we describe. We also developed a system to diagnose mineral nutrient disorders by visual symptoms in B. decumbens cv. Basilisk, and describe our results. We offer a list of priorities for further research.